Cryoballoon Ablation for Atrial Fibrillation - Jason G. Andrade, MD; Marc Dubuc, MD; Peter G. Guerra, MD; Laurent Macle, MD; Lena Rivard, MD; Denis Roy, MD; Mario Talajic, MD; Bernard Thibault, MD; Paul Khairy, MD, PhD (Indian Pacing and Electrophysiology Journal, 2012)
Focal point-by-point radiofrequency catheter ablation has shown considerable success in the treatment of paroxysmal atrial fibrillation. However, it is not without limitations. Recent clinical and preclinical studies have demonstrated that cryothermal ablation using a balloon catheter (Artic Front©, Medtronic CryoCath LP) provides an effective alternative strategy to treating atrial fibrillation. The objective of this article is to review efficacy and safety data surrounding cryoballoon ablation for paroxysmal and persistent atrial fibrillation. In addition, a practical step-by-step approach to cryoballoon ablation is presented, while highlighting relevant literature regarding: 1) the rationale for adjunctive imaging, 2) selection of an appropriate cryoballoon size, 3) predictors of efficacy, 4) advanced trouble-shooting techniques, and 5) strategies to reduce procedural complications, such as phrenic nerve palsy.